Patient–Health Care Provider Conversations About Prenatal Genetic Screening: Recommendation or Personal Choice - Colicchia, Laura C. (Obstet Gynecol, 2016)
OBJECTIVE: To assess how obstetric health care providers counsel patients regarding prenatal genetic screening, and how these conversations influence patients’ screening decisions. METHODS: This cohort study analyzed transcripts and audio recordings of 210 first prenatal visits, collected as part of a larger study on patient-provider communication. Conversations were coded in an iterative process to determine compliance with American College of Obstetricians and Gynecologists (the College) prenatal genetic screening recommendations and to identify recurrent themes. Chi-squared, nonparametric tests, and logistic regression were used to determine the effects of discussion elements on screening decisions. Qualitative analysis was performed for genetic screening content. RESULTS: The study included 210 patients and 45 health care providers. Health care providers offered genetic screening at 90% of visits; 78% of women chose genetic screening. Few conversations (1.5%) included all College-recommended topics. Inclusion of College-recommended topics did not affect women’s screening choices. Conversations about screening for fetal aneuploidy lasted 1.5 minutes on average (range 0.12 to 7.05 minutes). Recurrent themes identified included clarifying that screening results are not diagnostic (51% of conversations), emphasizing that screening is a personal choice (45% of conversations), and discussing how a woman might use genetic screening results to guide decisions about diagnostic testing or termination (37% of conversations). Health care providers described screening results as “high or low risk” in 67% of conversations discussing risk and quantitatively (ie, 1 in 100 or 1%) in 33%. CONCLUSIONS: Although the majority of patients were offered and underwent screening, most health care providers’ counseling did not adhere to College recommendations.